THE SOCIOLOGICAL PERSPECTIVE ON THE CAUSES AND MOTIVATIONS OF WORKPLACE BULLYING - Fadila Gheraibia (International Journal of Innovative Technologies in Social Science, 2025)
The phenomenon of bullying has seen a notable increase in recent times, becoming one of the key challenges individuals face, which hinders their ability to achieve their goals and meet their needs in life. Bullying is a negative behavior perpetrated by an individual or group against another individual or group, and it is most commonly observed in workplace environments. Due to the rising interest of researchers and academics in the phenomenon of workplace bullying, it is important to coordinate efforts to identify the real causes of this phenomenon, understand the factors that drive it, and seek prompt solutions to limit its spread. This is vital to reduce its impact on the achievement of both organizational objectives and human resources goals. The growing prevalence of workplace bullying has significant consequences on individual well-being and organizational efficiency, making it crucial to address this issue to foster a healthier, more productive work environment for all employees.